TINGKAT KEPUASAN PEMOHON PENSERTIFIKATAN TANAH PADA KANTOR PERTANAHAN - Soemargo, Amrieh Samad; Hubeis, Aida Vityala; Achsani, Noer Azam (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
Land Service has strategic significance for the benefit of society, especially in order to provide legal certainty and legal protection of a plot so that the public expects land services are easily accessible, cheap, fast, and give satisfaction to the users of the service. This study aimed to analyze the satisfaction level of the applicant, priority indicators to improve the satisfaction level of applicant, and the policies that must be taken to improve the satisfaction level of applicant to the quality of land services in Land Office of Badung District. The study was conducted using a cross sectional survey method on 120 applicants who transferred purchase and mortgage rights in the form of a questionnaire. The questionnaire is then processed with the validity and reliability analysis, gap analysis, and analysis of Importance Performance Analysis (IPA). The results showed that the quality of services provided by Land Office of Badung District did not meet the community satisfaction in Badung, and indicators that need to be prioritized to improve the satisfaction level of applicant is the timeliness of certificate completion. So the alternative policy that can be recommended in order to improve community satisfaction on quality service of land certification in Land Office of Badung District is to evaluate the service quality of land certification. Service quality was the first priority that has to be improved based on the result of this study in order to increase the quality of public services in the future.